Long-term improvements following a residential combined physical and psychological programme for chronic low back pain. Issue 2 (10th May 2021) - Wellburn, Shaun; Ryan, Cormac G; Coxon, Andrew; Dickson, Alastair J; Dickson, D John; Fatoye, Francis; Ferguson, Diarmaid; Green, Paul W; Greenhough, Charles; Hamilton, Sharon; Jess, Mary-Anne; Jones, Andrea; et al.
Abstract : Objectives: Evaluate the outcomes and explore experiences of patients undergoing a residential combined physical and psychological programme (CPPP) for chronic low back pain. Design: A longitudinal observational cohort design, with a parallel qualitative design using semistructured interviews. Setting: Residential, multimodal rehabilitation. Participants: 136 adults (62 male/74 female) referred to the CPPP, 100 (44 male/56 female) of whom completed the programme, during the term of the study. Ten (2 male/8 female) participated in the qualitative evaluation. Intervention: A 3-week residential CPPP. Outcome measures: Primary outcome measures were the STarT Back screening tool score; pain intensity—11-point Numerical Rating Scale; function—Oswestry Disability Index (ODI); health status/quality of life—EQ-5D-5L EuroQol five-Dimension-five level; anxiety—Generalised Anxiety Disorder-7; depression—Patient Health Questionnaire-9. Secondary outcome measures were the Global Subjective Outcome Scale; National Health Service Friends and Family Test;. Results: At discharge, 6 and 12 months follow ups, there were improvements from baseline that were greater than minimum clinically important differences in each of the outcomes (with the sole exception of ODI at discharge). At 12 months, the majority of people considered themselves a lot better (57%) and were extremely likely (86%) to recommend the programme to a friend. The qualitative data showed praise for the residential nature of the intervention and the opportunities for interaction with peers and peer support. There were testimonies of improvements in understanding of pain and how to manage it better. Some participants said they had reduced, or stopped, medication they had been taking to manage their pain. Conclusions: Participants improved, and maintained long term, beyond minimum clinically important differences on a wide range of outcomes. Participants reported an enhanced ability to self-manage their back pain and support for the residential setting.